2019
DOI: 10.1111/jfpp.14254
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate electric field on peroxidase activity, phenolic compounds and color during ohmic heating of sugarcane juice

Abstract: The influence of moderate electric field was evaluated during thermal treatment of sugarcane juice. Conventional and ohmic heating (OH) experiments at temperatures of 60 and 80°C were conducted to investigate the effect of frequency (0–105 Hz), waveform (sine, square, and triangle) and voltage gradient (0–16.7 V/cm) on inactivation of peroxidase (POD), phenolic compounds stability and color changes. Enzyme activity was significantly (p < .05) affected by OH; the nonthermal effects promoted POD activation at 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This feature is the main innovation of OH, making it a highly energy-efficient process suitable for rapid and uniform plant material processing. Using this technology, plants are not over-processed, and minimal changes in phytochemicals and color are produced [ 43 ].…”
Section: Industrial Methods Of Productionmentioning
confidence: 99%
“…This feature is the main innovation of OH, making it a highly energy-efficient process suitable for rapid and uniform plant material processing. Using this technology, plants are not over-processed, and minimal changes in phytochemicals and color are produced [ 43 ].…”
Section: Industrial Methods Of Productionmentioning
confidence: 99%
“…However, high voltage of PEF has been reported to increase degradation of some natural products, including phenolics. As phenolics donate electrons to other compounds, they respond to the alternate electric field [40]. Nevertheless, degradation was detected only by the thermal effect [40].…”
Section: Chemical Composition Of M Alba Leaf Extractsmentioning
confidence: 99%
“…As phenolics donate electrons to other compounds, they respond to the alternate electric field [40]. Nevertheless, degradation was detected only by the thermal effect [40]. Therefore, suitable conditions of PEF would result in enhanced extraction efficiency without degradation of biological compounds.…”
Section: Chemical Composition Of M Alba Leaf Extractsmentioning
confidence: 99%
“…Many studies on the effects of ohmic heating on degradation of phenolic compound and anthocyanin in processed foods have been reported (Brochier et al, 2019;Ferreira et al, 2019a;Hardinasinta et al, 2019;Loypimai et al, 2015;Makroo et al, 2017;Mercali et al, 2015Mercali et al, , 2013Sarkis et al, 2013Sarkis et al, , 2019Yildiz et al, 2009). Salari & Jafari (2020) conducted a review on the results of various studies and concluded that the effects of ohmic heating on the degradation of phenolic compounds and anthocyanin are not consistent since some researchers reported that ohmic heating resulted in higher degradation compared to conventional heating, while others reported that ohmic heating resulted in lower phenolic and anthocyanin degradation or similar to that of conventional heating.…”
Section: Introductionmentioning
confidence: 99%